The association between a vegetarian diet and cardiovascular disease (CVD) risk factors in India: the Indian Migration Study. - Krithiga Shridhar; Preet Kaur Dhillon; Liza Bowen; Sanjay Kinra; Ankalmadugu Venkatsubbareddy Bharathi; Dorairaj Prabhakaran; Kolli Srinath Reddy; Shah Ebrahim; Indian Migration Study Group (PLoS ONE)
Background Studies in the West have shown lower cardiovascular disease (CVD) risk among people taking a vegetarian diet, but these findings may be confounded and only a minority selects these diets. We evaluated the association between vegetarian diets (chosen by 35%) and CVD risk factors across four regions of India. Methods Study participants included urban migrants, their rural siblings and urban residents, of the Indian Migration Study from Lucknow, Nagpur, Hyderabad and Bangalore (n = 6555, mean age-40.9 yrs). Information on diet (validated interviewer-administered semi-quantitative food frequency questionnaire), tobacco, alcohol, physical history, medical history, as well as blood pressure, fasting blood and anthropometric measurements were collected. Vegetarians ate no eggs, fish, poultry or meat. Using robust standard error multivariate linear regression models, we investigated the association of vegetarian diets with blood cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL), triglycerides, fasting blood glucose (FBG), systolic (SBP) and diastolic blood pressure (DBP). Results Vegetarians (32.8% of the study population) did not differ from non-vegetarians with respect to age, use of smokeless tobacco, body mass index, and prevalence of diabetes or hypertension. Vegetarians had a higher standard of living and were less likely to smoke, drink alcohol (p<0.0001) and were less physically active (p = 0.04). In multivariate analysis, vegetarians had lower levels of total cholesterol (β =  -0.1 mmol/L (95% CI: -0.03 to -0.2), p = 0.006), triglycerides (β =  -0.05 mmol/L (95% CI: -0.007 to -0.01), p = 0.02), LDL (β =  -0.06 mmol/L (95% CI: -0.005 to -0.1), p = 0.03) and lower DBP (β =  -0.7 mmHg (95% CI: -1.2 to -0.07), p = 0.02). Vegetarians also had decreases in SBP (β =  -0.9 mmHg (95% CI: -1.9 to 0.08), p = 0.07) and FBG level (β =  -0.07 mmol/L (95% CI: -0.2 to 0.01), p = 0.09) when compared to non-vegetarians. Conclusion We found beneficial association of vegetarian diet with cardiovascular risk factors compared to non-vegetarian diet.